PERSPECTIVES IN PEDIATRIC PRACTICE - Valeriu Popescu (Amaltea Medical Publishing House, 2009)
Techological development in genetics and genomics provides unprecedented possibilities to identify the underlying molecular basis of many common diseases. With the availability of the human genome sequence and growing information on the most DNA variations combined with the molecular analysis on the RNA expression and protein levels, diseases might be characterized in the future at the molecular level. Describing gene function and the specific role of DNA, RNA and proteins in the disease process, provides novel diagnosis tools and treatment. Eventually, the goal is always to provide optimal therapy for each patient. Understanding how the unique genetic signature of an individual influences the risk and prognosis of disease is the basis of individualized medicine in the years to come (Broeckel et al, 2006). The author also underlines, the importance of a careful family history, complete clinical examination, routine laboratory investigations, specialized investigations for the diagnosis.